Pengolahan Limbah Cair Pabrik Kelapa Sawit dengan Metode Filtrasi dan Fitoremediasi Menggunakan Tanaman Eceng Gondok (Eichhornia Crassipes) - Ilmannafian, Adzani Ghani; Lestari, Ema; Khairunisa, Fitria (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2020)
ABSTRACTPalm oil mill effluent (POME) is a side product from oil palm processing activities with potential environmental pollution. Its smells, colored appearance contains high COD, BOD, and TSS values. Thus, the processing of POME is crucial. In treating this wastewater, filtration and phytoremediation methods can be applied. This study aimed to evaluate the performance of the POME treatment using filtration and phytoremediation methods using water hyacinth (Eichhornia crassipes). This research method includes a sampling process, tub reactor construction with four filter ingredients (sand, gravel, coconut fiber, and sponge), the dilution of POME (concentration of 100%, 75%, and 50%), phytoremediation, filtering and testing of sample parameters. The parameters tested were BOD, COD, TSS, pH, and physical properties, including color, smell, and turbidity. The results of this study showed that the application of POME treatment with water hyacinth was not yet effective, supported by the following research results of the treatment concentration of 100%, 75%, and 50% with BOD levels respectively 894.7 mg/l, 304.15 mg/l, and 77.03 mg/l, COD levels respectively 4,320 mg/l, 1,120 mg/l, and 440 mg/l, TSS levels were 400 mg/l, 200 mg/l and 0 mg/l respectively. While, pH results for those treatments are 8,8 and 9 respectively.Keywords: filtration, liquid waste, phytoremediation, water hyacinthABSTRAKKegiatan operasional Pabrik Kelapa Sawit menghasilkan produk samping (By-Product) salah satunya limbah cair yang berbau, berwarna, mengandung nilai COD, BOD serta TSS yang tinggi berpotensi mencemari lingkungan, sehingga pengolahan limbah cair di pabrik kelapa sawit sangat penting. Filtrasi dan fitoremediasi adalah metode yang dapat digunakan dalam mengolah limbah cair pabrik kelapa sawit. Penelitian ini bertujuan untuk menganalisis hasil pengolahan limbah cair pabrik kelapa sawit dengan metode filtrasi dan fitoremediasi menggunakan tanaman eceng gondok (Eichhornia crassipes). Metode penelitian ini meliputi proses sampling, membuat bak reaktor berukuran 60 cm x 40 cm x 40 cm dengan 4 media penyaring (pasir, kerikil, serabut kelapa dan spons), kemudian melakukan pengenceran limbah cair pabrik kelapa sawit dengan konsentrasi 100%, 75% dan 50%, fitoremediasi, penyaringan dan pengujian sampel parameter BOD, COD, TSS, pH dan Uji sifat fisik meliputi warna, aroma dan kekeruhan. Hasil penelitian ini menyatakan bahwa aplikasi pengolahan limbah PKS dengan tanaman enceng gondok belum efektif, dengan ditunjang hasil penelitian sebagai berikut : 100%, 75%, dan 50% dengan kadar BOD berturut-turut 894,7 mg/l, 304,15 mg/l, dan 77,03 mg/l, kadar COD berturut-turut 4.320 mg/l, 1.120 mg/lÃ‚Â dan 440 mg/l, kadar TSS berturut-turut 400 mg/l, 200 mg/lÃ‚Â dan 0 mg/lÃ‚Â dan pH berturut-turut 8,8 dan 9.Kata kunci: eceng gondok, filtrasi,Ã‚Â fitoremediasi, limbah cairÃ‚Â